PENGARUH KETERAMPILAN DASAR GURU DALAM MENJELASKAN TERHADAP PEMAHAMAN SISWA PADA MATA PELAJARAN PAI-BP DI KELAS XI MIPA 2 SMA NEGERI 1 SENTAJO RAYA - Alfiantoni Alfiantoni; Sopiatun Nahwiyah; Alhairi Alhairi (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2023)
The skill of explaining is a skill in presenting information verbally by the teacher to build solid student understanding of the learning material. From the results of the pre-research on class XI MIPA 2 students at SMA Negeri 1 Sentajo Raya, it was found that: the majority of students could not answer questions and looked confused when asked again about the material that had been explained by the teacher. Then the majority of these students also could not provide examples of the application of the material in everyday life and could not re-explain the material that had been delivered. This study aims to determine whether there is an effect of teacher basic skills in "explaining" on students' understanding of PAI-BP subjects in class XI MIPA 2 SMA Negeri 1 Sentajo Raya. This type of research is quantitative, with data collection techniques using questionnaires and documentation. Then the data analysis technique uses Simple Linear Regression with a sample of 25 people. The results showed that there was no effect of the basic skills of the PAI-BP teacher in "explaining" the material as the X variable on students' understanding as the Y variable because the T-Test obtained an equation with a tcount value of 0.704 which is less than the ttable value of 2.069. Likewise in the significance test where the value (Sig.) 0.488 is greater than the probability of 0.05.